(untitled) (Scientific journal of the Fergana State University, 2023)
Language as a means of communication is associated with culture by numerous and complex ties. Linguistic contacts take place both during direct contacts of peoples and in their absence, at the same time representing an important part of mediated contacts of cultures. The article discusses the beginning of the development of Russian-English language contacts and analyzes the language contacts between languages that influence each other.